Pengaruh Institutional Ownership dan Foreign Ownership terhadap Tax Avoidance dengan Transfer Pricing sebagai Variabel Mediasi (Studi Empiris pada Perusahaan Industri Kelapa Sawit di BEI 2020–2024) - Ilham Amanah Rangga Kancana; Lin Oktris (Jurnal Proaksi, 2025)
Purpose – This study aims to examine the effect of institutional ownership and foreign ownership on tax avoidance with transfer pricing as a mediating variable.Methodology – The research sample includes 18 palm oil companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The analysis was conducted using panel data regression with Common, Fixed, and Random Effect models, followed by Chow, Hausman, and LM tests. Mediation testing was carried out using the Baron–Kenny approach, Sobel test, and wild cluster bootstrap-t procedure.Findings – The results show that institutional ownership has no significant effect on either tax avoidance or transfer pricing. In contrast, foreign ownership has a significant positive effect on transfer pricing, while transfer pricing has a negative effect on tax avoidance. Mediation testing indicates that transfer pricing does not mediate the relationship between institutional ownership and tax avoidance, but the wild cluster bootstrap-t test suggests a marginal negative mediation between foreign ownership and tax avoidance.Theoretical and Policy Implications – The findings indicate that ownership structure can shape the pattern of related-party transactions, and more comprehensive transfer pricing disclosure is aligned with lower levels of tax avoidance. In practical terms, this study encourages strengthening risk-based supervision and the quality of related-party transaction documentation.Novelty – This study provides new empirical evidence in the Indonesian palm oil industry by combining various mediation approaches, showing that transfer pricing disclosure can function as a compliance mechanism rather than merely as a tool for tax avoidance.